Tariffs and Danish exports: Insights from three decades of microdata - Henrik Yde Andersen; Thomas Krause (Danmarks Nationalbank, 2025)
Foreign tariffs on Danish exports have fallen by more than half over the past three decades, yet substantial differences remain across products. Drawing on historical product-level tariff data, foreign trade statistics, and firm-level accounts, our analysis shows that exports of Danish goods decline when tariffs rise. In contrast, employment and investment among Danish exporters show no clear changes. These patterns suggest that firms adapt to higher tariffs, either by seeking new trading partners or rerouting exports through third countries, helping to cushion the broader economic impact.
Keywords: 330